(untitled) (diségno, 2026)
Interest in the pictorial representation of architectural space has deep roots in classical and Roman antiquity and has developed as a form of decoration or as an integration of built architecture with virtual special constructions, continuing into the modern age. In the first half of the fourteenth century, a substantial evolution took place: painted architecture was emancipated from its traditional role as a mere backdrop, typical of the Byzantine tradition, to acquire volumetric and perspectival consistency, capable of actively interacting with the symbolic and narrative construction of the scene. This transformation can largely be attributed to Giotto, who reinterpreted the Roman figurative heritage in an original way, drawing from a vast repertoire of classical sources and integrating his pictorial compositions with architectural models of contemporary buildings. The cycle of the Stories of Saint Francis, attributed to Giotto and his workshop and executed between the late thirteenth and early fourteenth centuries in the Upper Basilica of Assisi, represents the first fully realized example of this new approach. This study constitutes an initial reflection within a broader research project based on a high-accuracy digital survey of the decorated interior surfaces of the basilica. The pictorial cycle is thus examined not only as an ordering principle of real space but also as an opportunity to explore drawing as a tool for knowledge, analysis, and mediation between architectural conception and figurative narration.